Inovasi Pemberdayaan Masyarakat Berbasis Sumber Daya Pangan di Sekitar Wilayah Operasional PT. Pertamina Asset 3 Subang Field - . Sumardjo; Adi Firmansyah (Institut Pertanian Bogor, 2015)
Around the company's operations are often found powerlessness problems of society. The company through the CSR program are required to contribute to addressing the problems, so that potential conflicts can be managed. The program objectives are: designing community development that can become self-sufficient rural development model as a development movement program that can mobilize local resources; promoting independence of society through the productive activities, and develop a model of the institutionalization of the development of self-reliance. The program has been implemented by the PRA method, which location in Subang and Karawang. Programs have been conducted on four target groups, namely mushroom group (10 members), the group of sheep (25 members), food group (35 members), and Assolahiyah group (66 members). Community empowerment program has resulted in innovation, as follows: (1) Zero waste systems in mushroom group, the group has use of straw for mushroom growing media; (2) Processing of various types of food made from mushrooms, such as mushroom noodles and mushroom bread; (3) Utilization of sheep dung into organic fertilizer; (4) Utilization of straw for animal feed; (5) An innovative enclosure design to minimize the smell of dung, environmental pollution, and easy to clean; and (6) The integration of nonformal education with entrepreneurship education. Conclusion: based on the development of group target (independence, participation, and networking), group Assolahiyah is a fastest, and the lowest is food group; and participatory program, is effectively encouraging the growth and development of innovation/new practices which generated by community.